An Analysis of Students’ Speaking Self-Efficacy in Collaborative Learning - Gustina, Ika; Atmowardoyo, Haryanto; Korompot, Chairil Anwar (Celebes Journal of Language Studies, 2024)
This research aims to find out the student’s speaking self-efficacy in collaborative learning. This research is qualitative research with a case study type, data collection using observation and interview. This research used the case study method. The participants of this research are students of MA Yapit Taretta. This research was conducted students at MA Yapit Taretta. The results showed: 1) Self-efficacy affects how people set goals, cope with challenges, and persist in the face of obstacles. 2) Collaborative learning environments offer a conducive setting for learners to enhance their speaking skills through repeated practice and constructive feedback, ultimately fostering greater confidence and proficiency. The statement underscores the psychological and educational benefits of collaborative learning environments in enhancing student confidence and reducing anxiety. 3) The effectiveness of collaborative learning activities in improving student confidence in speaking.